UHT metamorphism. Can integrated thermobarometry and geochronology quantify lower crustal processes? - Mitchell, Ruairidh J. (Curtin University, 2019)
The Eastern Ghats Province cooled at 0.34 ± 0.09 °C/Ma from ~6.8–8.3 kbar, 1000°C between c. 1000–880 Ma, and was reheated to >900 °C at c. 550–500 Ma. This reflects a period of burial in the deep crust of an orogen with high radiogenic heat production and slow rates of erosion. Additionally, local equilibrium can persist in metamorphic rocks at >900 °C, should solid phases be chemically and physically isolated from melt.